Subwavelength Plasmonic Waveguides and Plasmonic Materials - Ruoxi Yang; Zhaolin Lu (International Journal of Optics)
With the fast development of microfabrication technology and advanced computational tools, nanophotonics has been widely studied for high-speed data transmission, sensitive optical detection, manipulation of ultrasmall objects, and visualization of nanoscale patterns. As an important branch of nanophotonics, plasmonics has enabled light-matter interactions at a deep subwavelength length scale. Plasmonics, or surface plasmon based photonics, focus on how to exploit the optical property of metals with abundant free electrons and hence negative permittivity. The oscillation of free electrons, when properly driven by electromagnetic waves, would form plasmon-polaritons in the vicinity of metal surfaces and potentially result in extreme light confinement. The objective of this article is to review the progress of subwavelength or deep subwavelength plasmonic waveguides, and fabrication techniques of plasmonic materials.